Mapping the big data analytics in sharing economy: A bibliometric literature review - Yang, Yuxue; Su, Xiang; Yao, Shuangliang; Tao, Chen (Frontiers in Environmental Science, 2022)
This paper offers a holistic review of the role of big data analytics in sharing economy (SE). Academic literature in this field is analyzed to show the theoretical foundation, important papers, and key themes underlying the field by using various bibliometric analysis tools. We conduct a citation and co-citation analysis on literature concerning big data analytics in sharing economy, which published in the 12-year period from 2010-2021. A total of 205 papers were screened from Web of Science (WoS) database for our analysis. In the citation analysis, we depend on the degree centrality and betweenness centrality to identify 48 important papers. In the co-citation analysis, four major research themes are identified: sustainable business model, efficient match-making, trust building and innovation and value cocreation. The research also highlights future research directions and critical areas for the application of big data analytics in the SE context, which may help to produce in-depth studies.